The Spatial Distribution of Precipitation in Northwest China. (1st September 2014) - Zhao, Chuancheng; Yao, Shuxia; Liu, Jun; Wang, Jian
Abstract : Northwestern China has an extremely complex climate due to the varied terrain and complexities of climate change where the environment is sensitive to both regional and global climate change. We employed the Mann-Kendal test to investigate trends of precipitation distributions using annual, seasonal, and monthly data records from 1960 to 2008. On the whole, the variations in precipitation patterns are more complex than those for temperature. The trends of annual, seasonal, and monthly precipitation have shown remarkable differences between the east and west. In the west such as in northern Xinjiang and western Qinghai, the variation is a significant increase, consistent with the temperature change, whereas in the east such as in eastern Gansu, and southern Shaanxi, the variation is a remarkable decrease, opposite to the change observed in temperatures.